2020
DOI: 10.1109/access.2020.3025938
|View full text |Cite
|
Sign up to set email alerts
|

Human Daily Activity Recognition Performed Using Wearable Inertial Sensors Combined With Deep Learning Algorithms

Abstract: This study proposed a wearable device capable of recognizing six human daily activities (walking, walking upstairs, walking downstairs, sitting, standing, and lying) through a deep learning algorithm. Existing wearable devices are mainly watches or wristbands, and almost none are to be worn on the waist. Wearable devices in the forms of watches and wristbands are unfriendly to patients who are critically ill, such as patients undergoing dialysis. Patients undergoing dialysis have artificial blood vessels on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…They used the UCI-HAR dataset, a real-world extrasensory dataset [89] and the DCASE 2017 dataset. Yen et al [57] suggested a CNN-based HAR framework using the smartphone-derived UCI-HAR public dataset and selfcollected data from wearable sensors. Wan et al In [59], a sparse AE (SAE) was used to automatically learn features, and based on this concept, a smartphone-based HAR framework was proposed.…”
Section: A Deep Learning For Harmentioning
confidence: 99%
See 1 more Smart Citation
“…They used the UCI-HAR dataset, a real-world extrasensory dataset [89] and the DCASE 2017 dataset. Yen et al [57] suggested a CNN-based HAR framework using the smartphone-derived UCI-HAR public dataset and selfcollected data from wearable sensors. Wan et al In [59], a sparse AE (SAE) was used to automatically learn features, and based on this concept, a smartphone-based HAR framework was proposed.…”
Section: A Deep Learning For Harmentioning
confidence: 99%
“…In comparison with a fully connected layer, a convolution layer has much fewer parameters due to sparse connectivity and weight sharing, thereby minimizing the possibility of overfitting. However, due to the tremendous popularity of traditional CNNs in HAR, the recently proposed CNN-based HAR models adopt 1-2 fully connected layers as classifiers [57,87]. Although fully connected layers can adequately perform classification, various parameters lead to the risk of overfitting.…”
Section: A Cnnsmentioning
confidence: 99%
“…HAR technology using wearable devices and learning algorithms has already achieved several successful applications. Yen et al proposed an automatic CNN feature extraction method combined with a wearable inertial sensor to improve the accuracy of daily activity recognition [4]. Lawal and BanoI developed a method of establishing a frequency image for an original signal to improve the overall recognition performance [10].…”
Section: Related Workmentioning
confidence: 99%
“…Following the popularization and optimization of intelligent electronic devices and computer systems, human activity recognition (HAR) via wearable devices has been attracting research attention for decades. HAR technology has been applied to various scenarios in the fields of medical care, military security, health service and infotainment, and new application requirements have even emerged in the context of COVID-19 [1][2][3][4][5][6][7][8]. In comparison with vision-based activity recognition, wearable sensors in human activity recognition provide more possibilities for human and mobile devices to interact due to their low cost, small size, strong computing ability and privacy protection, which also serve as the hardware support for the experimental data collection stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation